ANALISIS PENGARUH MUTU PELAYANAN AKADEMIK TERHADAP TINGKAT KEPUASAN MAHASISWA DI SEKOLAH TINGGI TEKNOLOGI CIPASUNG - Ernawati; Mauly Sriwahyuni Yusuf (LPPM Sekolah Tinggi Teknologi Cipasung, 2023)
Cipasung College of Technology is a private university, founded in 1997 located in Tasikmalaya Regency. So far, the Cipasung High School of Technology has not known the effect of the quality of academic services that have been provided to students. Therefore, a research was conducted on the effect of academic service quality on student satisfaction at the Cipasung High School of Technology, Industrial Engineering Study Program. This study was analyzed using Multiple Linear Regression Analysis. Based on the results of the simultaneous multiple linear regression test, it was found that the Quality of Academic Services consisting of Tangibles (physical evidence), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Assurance), and Empathy (empathy) together has a significant effect on student satisfaction (Y). Partially only the Empathy Variable (X₅) has a significant effect on student satisfaction. while service quality variables such as Tangibles (physical evidence), Realiability (reliability), Responsiveness (responsiveness) and Assurance (guarantee) do not have a significant effect on student satisfaction.